Surface tension of viscous biopolymer solutions measured using the du Nouy ring method and the drop weight methods - Lee, Boon Beng; Chan, Eng Seng; Pogaku, Ravindra, Prof. Dr.; Tanveer, Ahmad Khan, Dr. (Springer-Verlag, 2013)
Link to publisher's homepage at http://link.springer.com/